Performance evaluation of a flatbed maize dryer with a biomass heat source - Akowuah, JO; Boateng, HA; Akrofi, G Obeng; Maier, DE (International Journal of Agricultural Research, Innovation and Technology, 2022)
The technical performance of a 3-tonne capacity flatbed grain dryer was assessed based on its drying rate and drying efficiency. In addition, the quality of maize grains dried in the drying system was investigated through stress-crack analysis and germination test. Maize grains at an initial moisture content of 18.4% ± 0.1% (wb) were dried to a safe moisture content of 13.3% ± 0.2% (wb) in 5 hours, resulting in a drying rate of 1.02%/h at a drying efficiency of 67.35%. The average temperature observed in the plenum (55.8°C±1.5°C) was about twice higher than the ambient temperature during the drying period. The use of the flatbed dryer did not have any adverse effect on the viability of grains dried with a stress-crack index of 75 and percentage germination of 90%. This study demonstrated the viability of using the flatbed biomass-assisted dryer for drying maize and can reduce post-harvest losses of maize at the smallholder level. Int. J. Agril. Res. Innov. Tech. 11(2): 37-41, Dec 2021